Anggri Indraprasti PESONA KERATON SUMENEP DALAM DESAIN CINDERAMATA OLEH UKM KAYU UKIR KARDULUK, MADURA - Anggri Indraprasti; Imam Santosa; Prasetyo Adhitama (PROSIDING: SENI, TEKNOLOGI, DAN MASYARAKAT, 2020)
Sumenep is a town located at the east part of Madura Island, East Java Province. It has a distinctive historyabout the Keraton and its people. Build in 1762, the Keraton of Sumenep is the only cultural heritage building,existed in East Java which is categorized as a ‘palace’. The people of Sumenep also inherit the skill of craftingwood, specifically in carving. The village of Karduluk is the only local craft industry in Madura which producelocal wooden furniture with its Madurese and Keraton’s flair. As a developing town with its rich cultural andhistorical background of the Keraton, Sumenep also needs to develop its wooden craft industry. This researchstudies the potential of the wooden craft industry of Karduluk in developing distinctive designs which cancontribute to the region’s tourism industry. One of the products that could contribute significantly is the localsouvenir. May it be the official souvenir of the head of the Sumenep Region or the contemporary souvenir forthe global tourism consumer. Using the ‘4D design method’ on developing products, define, design, developand disseminate, this research uncover the hidden treasures of the Keraton’s beauty from the wooden craftpeople of Karduluk.